(untitled) (Research, Society and Development, 2021)
This article aimed to compare body image and sexual satisfaction in obese women and women undergoing bariatric surgery for at least 8 months; check the self-perception of both samples in relation to weight; to verify whether there is a correlation between satisfaction with body image and sexual satisfaction between the two groups. 258 women in an affective/sexual relationship participated, 100 of which were classified as having grade II obesity and 158 were in a condition after bariatric surgery. All participants answered the following instruments: Sociodemographic Characterization Questionnaire; Body Shape Questionnaire and the Sexual Satisfaction Scale for Women (SSS-W). For data analysis, descriptive statistical analysis, t test, ANOVA and Pearson correlation test were performed. As a result, it was found that the sexual satisfaction score in the SSSW was 106.57 (women undergoing surgery) and 102.98 (obese), with no significant difference (p > 0.05). In terms of body image satisfaction, among women with surgery, 47.46% were classified as satisfied, 25.95% as mildly dissatisfied, 18.36% as moderately dissatisfied and 8.23% as severely dissatisfied. Among obese women, 14% were satisfied, 15% were mildly dissatisfied, 43% were moderately dissatisfied and 28% were severely dissatisfied with their image. A statistically significant negative correlation (r = 0.40 p = 0.001) was found between Sexual Satisfaction and Body Image. It is concluded that, regardless of weight, there is a tendency that the greater the concern a woman has with her body image, the lower her sexual satisfaction will be.